Epigenomic Regulators Elongator Complex Subunit 2 and Methyltransferase 1 Differentially Condition the Spaceflight Response in Arabidopsis - Paul, Anna-Lisa; Haveman, Natasha; Califar, Brandon; Ferl, Robert J. (Frontiers in Plant Science, 2021)
Background: Plants subjected to the novel environment of spaceflight show transcriptomic changes that resemble aspects of several terrestrial abiotic stress responses. Under investigation here is whether epigenetic modulations, similar to those that occur in terrestrial stress responses, have a functional role in spaceflight physiological adaptation. The APEX-04-EPEX (Advanced Plant Experiment-04 – Epigenetic Expression) experiment examined the role of cytosine methylation in spaceflight adaptation. The experiment was conducted onboard the International Space Station (ISS), and evaluated the spaceflight-altered, genome-wide methylation profiles of two methylation-regulating gene mutants (methyltransferase 1 (met1-7) and elongator complex subunit 2 (elp2-5)) along with wild-type Col-0 control. Results: The elp2-5 plants suffered in their physiological adaptation to spaceflight in that their roots failed to extend away from the seed and the overall development of the plants was greatly impaired in space. The met1-7 plants suffered less, with their morphology affected by spaceflight in a manner similar to that of the Col-0 controls. The differentially expressed genes in spaceflight were dramatically different in the elp2-5 and met1-7 plants compared to Col-0, indicating that the disruptions in these mutants resulted in a reprogramming of their spaceflight responses, especially in elp2-5. Many of the genes comprising the spaceflight transcriptome of each genotype were differentially methylated in spaceflight. In Col-0 the majority of the differentially expressed genes were representative of the now familiar spaceflight response, which includes genes associated with cell wall remodeling, pathogen responses and ROS signaling. However, the spaceflight transcriptomes of met1-7 and elp2-5 each presented patterns of differentially expressed genes that are almost completely different than Col-0, and to each other. Further, the differentially expressed genes of the mutant genotypes suggest a more severe spaceflight stress response in the mutants, particularly in elp2-5. Conclusion: Arabidopsis physiological adaptation to spaceflight engages differential DNA methylation in an organ-specific manner, and disruption of methylation mechanisms adversely affects the spaceflight response. Disruption of methyltransferase function does not dramatically affect spaceflight growth or morphology, yet met1-7 reprograms the spaceflight transcriptomic response in a unique manner. Disruption of elp2-5 results in poor development in spaceflight grown plants, together with a diminished, dramatically reprogrammed transcriptomic response.